High Dimensional Model Representation (HDMR) for Exponential Function with Quadratic Argument - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2008)
In this work we develop analytical formulation for the first three terms of the HDMR expansion for an exponential function with quadratic argument.
Keywords: Multivariate functions; Exponential function with quadratic arguments; High Dimensional Model Representation